Обставини, що підлягають з’ясуванню під час розслідування резонансних статевих кримінальних правопорушень - Пчеліна, О. В.; Pchelina, O. V.; Пчелін, В. Б.; Pchelin, V. B.; Пчеліна Оксана Василівна; Віталій Пчелін (Науковий вісник Ужгородського національного університету. Серія : Право. - 2024. - Вип. 81, ч. 3. - С. 144-149, 2024)
Наголошено, що обставини, що підлягають з’ясуванню, є обов’язковим структурним елементом методики розслідування резонансних статевих кримінальних правопорушень, бо їх встановлення, своєю чергою, є передумовою досягнення мети кримінального процесуального пізнання та вирішення завдань кримінального провадження. Наведено перелік обставин, що підлягають з’ясуванню під час здійснення досудового розслідування таких різновидів резонансних сексуальних кримінальних правопорушень, як: зґвалтування та сексуальне насильство, вчинене групою осіб та/ чи батьками, особами, які їх замінюють, та/чи щодо неповнолітніх, малолітніх; домагання дитини для сексуальних цілей; проведення видовищного заходу сексуального характеру за участю неповнолітньої особи. Запропоновано систематизувати обставин, що підлягають з’ясуванню під час досудового розслідування резонансних статевих кримінальних правопорушень з урахуванням змішаного (кримінального процесуального та криміналістичного) критерію. Виокремлено й охарактеризовано наступні групи обставин, що підлягають з’ясуванню під час досудового розслідування резонансних статевих кримінальних правопорушень: обставини, що характеризують подію кримінального правопорушення; обставини, що характеризують особу правопорушника; обставини, що характеризують особу потерпілого; інші обставини.

In the article has been emphasized that the circumstances to be ascertained are a mandatory structural element of the methodology of investigating high-profile sexual criminal offenses, because their establishment, in turn, is a prerequisite for achieving the goal of criminal procedural knowledge and solving the tasks of criminal proceedings. It has been given the list of circumstances to be ascertained during the pre-trial investigation of such types of high-profile sexual criminal offenses as: rape and sexual violence committed by a group of persons and/or parents, persons who replace them, and/or against minors; molestation of a child for sexual purposes; conducting a spectacular event of a sexual nature with the participation of a minor. It has been found that different approaches to the systematization of the circumstances to be ascertained during the pre-trial investigation have been formed in forensic science. They are mainly determined by the specifics of the mechanism of committing a specific type of criminal offense, which undoubtedly affects the formation of investigative and other evidentiary information. An analysis of scientific approaches to determining the range of circumstances to be ascertained (established) during the investigation of sexual criminal offenses has been carried out. It has been proposed to systematize the circumstances to be ascertained during the pre-trial investigation of high-profile sexual criminal offenses taking into account the mixed (criminal procedural and forensic) criterion. The following groups of circumstances to be ascertained during the pre-trial investigation of high-profile sexual criminal offenses have been singled out and characterized: circumstances characterizing the event of a criminal offence; circumstances characterizing the person of the offender; circumstances characterizing the person of the victim; other circumstances.

Предложено систематизировать обстоятельства, подлежащих выяснению в ходе досудебного расследования резонансных половых уголовных правонарушений с учетом смешанного (уголовного процессуального и криминалистического) критерия. Выделены и охарактеризованы следующие группы обстоятельств, подлежащих выяснению в ходе досудебного расследования резонансных половых уголовных правонарушений: обстоятельства, характеризующие событие уголовного правонарушения; обстоятельства, характеризующие личность правонарушителя; обстоятельства, характеризующие личность потерпевшего; другие обстоятельства.
Circumstances to be ascertained during the investigation of high profile sexual criminal offenses
Keywords: обставини, що підлягають з’ясуванню; досудове розслідування; кримінальне провадження; статеві кримінальні правопорушення; резонансні кримінальні правопорушення; зґвалтування; сексуальне насильство; домагання дитини для сексуальних цілей; проведення видовищного заходу сексуального характеру; circumstances to be ascertained; pretrial investigation; criminal proceedings; sexual criminal offenses; high-profile criminal offenses; rape; sexual violence; molestation of a child for sexual purposes; conducting a spectacular event of a sexual nature; обстоятельства, подлежащие выяснению; досудебное расследование; уголовное производство; половые уголовные правонарушения; резонансные уголовные правонарушения; изнасилование; сексуальное насилие; домогательство ребенка для сексуальных целей; проведение зрелищного мероприятия сексуального характера